Analysis Of Potential Bankruptcy In Blue Bird Tbk And Transindo Utama Tbk Using Springate And Grover Models - Indah Sariwati; Fachruzzaman Fachruzzaman (UNIVED Press, 2024)
Financial statement analysis is very important for companies. By analysing financial statements, the potential for bankruptcy can be known from the start. Financial statements serve as a source of information for creditors, investors, employees, and other parties in need.In industry 4.0, everything is online, even transport. The object of this research is PT Blue Bird Tbk. and PT Transindo Utama Tbk. The purpose of this study is to determine the company's financial performance in the last five years and potential bankruptcy. The analysis method in this study is the Springate model and the Grover model.The conclusion of this study is that using the Springate model, PT Blue Bird Tbk. in 2018 shows a healthy financial condition, while in 2019-2022 it shows potential bankruptcy. PT Transindo Utama Tbk. in 2018, 2019, 2020, 2022 shows potential bankruptcy, while in 2021 the financial condition is healthy. Then using the Grover model, PT Blue Bird Tbk. shows no potential bankruptcy. PT Transindo Utama Tbk. shows potential bankruptcy in 2018-2020, while in 2021 and 2022 the financial condition is healthy.